SISTEM MONITORING BUDIDAYA PERIKANAN BERBASIS IOT FISH FEEDER SEBAGAI IMPLEMENTASI SMART FARMING - Sudibyo, Heri; Yuniko, Fauzi Tri; Fadel, Ahmad; Lesmana, Lido Sabda; Efendi, Raimon (Institut Bisnis dan Teknologi Pelita Indonesia, 2024)
Aquaculture faces various challenges, including uncertainty in timely and appropriate feeding, which can affect fish health and productivity. This research aims to design and implement an Internet of Things (IoT)-based aquaculture monitoring system equipped with an automatic fish feeder. The research method used in this research is the prototype method. The automatic fish feeder prototype is developed and integrated with sensors and IoT devices. Data was collected through system testing at a real aquaculture site, by monitoring water quality parameters and feeding schedules using a web-based application. The results showed that the IoT-based monitoring system was able to provide real-time information on feeding status and pond conditions. The automatic fish feeder successfully delivers feed according to fish needs, reduces feed wastage, and improves pond environmental quality.